Transpubic Urethroplasty: A Single Center Experience - Raj Kumar Mathur; Niraj Shriram Tiwari; Sudharshan A. Odiya (Advances in Urology)
Objective. To evaluate the long-term results of transpubic urethroplasty for pelvic fracture urethral distraction defects. Patients and Methods. Sixteen patients who had undergone transpubic urethroplasty for posttraumatic complex posterior urethral disruptions between 2007 and 2013 were analyzed retrospectively and prospectively. Patients were followed up for a mean (range) of 24 (6–60) months by history, urinary flow rate estimate, retrograde urethrography, and voiding cystourethrography. Results. The mean age of the patients was 30.4 years. The estimated radiographic stricture length before surgery was 4.3 cm. Transpubic urethroplasty was successful in 14 out of 16 patients. Postoperative complications were recurrent stricture (12.5%), urethrocutaneous fistula (12.5%), incontinence (31.25%), impotence (25%), and wound infection (18.75%). Failed repairs were successfully managed endoscopically in one patient and by perineal anastomotic repair in the other, giving a final success rate of 100%. Five out of 16 patients were incontinent of which 3 of them resolved and 2 had permanent incontinence. Impotence was seen in 4 out of 16 patients. There were no reported complications of pubectomy in any of our patients. Conclusions. Though considered obsolete now, transpubic urethroplasty for complex posterior urethral disruptions is still a viable alternative with excellent results and minimal morbidity.